(untitled) (Research, Society and Development, 2021)
Objective: The objective this review was to identify the current range of shear bond strength values (SBS) that are clinically acceptable based on a synthesis of the studies published in 20 years that evaluated the SBS of brackets bonded to dental enamel with emitter diode light photo activators and whether damage to the enamel has been reported after the test. Methodology: A search strategy was developed for the selection of articles published from 1999 to 2019 in the PubMed/MedLine electronic database. In addition to reading the titles, keywords and summaries of the studies found, the studies were also obtained for the reading of the methodologies and identification of the inclusion and exclusion criteria. Results: The search for scientific articles resulted in 580 studies, but only 14 were selected based on the pre-established criteria. Ten presented methodological quality to be included in this integrative review, and the mean SBS found was 14,05 MPa with a standard deviation of ± 6,52 MPa (range from 7,53 to 20,57 MPa). Conclusion: In conclusion, it was observed that the range of shear bond strength values (5,9 to 7,8 MPa) and taken as a parameter by most authors until now is outdated, since higher values of SBS are feasible without, however, causing dental enamel damage after the debonding of the bracket.